Registros de mamíferos presentes en el Área Marina Costera Protegida de Múltiples Usos Lafken Mapu Lahual, sur de Chile - Rau, Jaime R.; Oyarzún, Carlos; Vilugrón, Jonnathan; Cursach, Jaime A.; Tobar, Claudio N.; Provoste, Marcelo; Abarzúa, Javiera (Revista de Biología Marina y Oceanografía, 2021)
The Lafken Mapu Lahual Coastal Marine Protected Area of Multiple Uses (Lafken Mapu Lahual), Osorno coast, southern Chile, is one of the first protected areas created in Chile during 2006, but only in 2019 its Management Plan was presented. This study provides information on its marine mammal species to be used in future biodiversity monitoring plans. The sighted mammals were recorded and counted through 18 navigation tracks and one observation point in the 2014-2015 austral breeding season. Five species were recorded systematically (one whale species, two dolphin species, one marine otter species and a one sea lion species). Two of them (Lontra felina and Balaenoptera musculus) are classified by the IUCN in the conservation category corresponding to Endangered. Laken Mapu Lahual is an important area for the species of whales that use it for their migratory route to the south of Chile.